انتشار الحساسية العاجية وتوزعها وشدتها لدى مراجعي العيادات حول السنية - داود, هاشم محمد (Latakia University Journal -Medical Sciences Series, 2019)
تعتبر فرط الحساسية العاجية إحدى أهم المشكلات التي تواجه طب الأسنان الحديث لما تسببه من إزعاج متواصل ومعاناة يومية للمرضى وبالرغم من اعتبارها حالة مبهمة لتعدد أسبابها وعدم وضوح آلية حدوثها بدقة فهي لم تحظ بالدراسة الوافية هدفت هذه الدراسة إلى تحديد انتشار وتوزع وشدة ومدة ظهور فرط الحساسية العاجية لدى مرضى النسج حول السنية عن طريق دراسة علاقتها بالاستجواب وباختبار الإثارة بتيار هوائي وبالتحريض الميكانيكي وربطها مع بعض العوامل المسببة المحتملة (الانحسار اللثوي –حالة الصحة الفموية). بالإضافة إلى الفحص التقليدي حول السني تم تحليل معطيات الاستجواب ونتائج اختبار الإثارة بتيار هوائي وبالتحريض الميكانيكي لظاهرة فرط الحساسية العاجية لـ97 1 مريضاً من مراجعي عيادات قسم أمراض النسج حول السنية في كلية طب الأسنان تتراوح أعمارهم بين 17-65 سنة من خلال استبيان وفحوصات سريرية فموية, كما تمت دراسة الانحسار اللثوي وحساب مشعر اللويحة. أظهرت النتائج تواترا لفرط الحساسية العاجية لدى 171 مريضا أي بنسبة 86,8%, وهي تتعلق بمعطيات الاستجواب (المعطيات التقديرية غير الموضوعية) وبنسبة 66% (130) وفقا لمعطيات الفحوص السريرية داخل الفموية, كما توصلت إلى أن فرط الحساسية العاجية تزامنت مع الانحسار اللثوي لدى (82) مريضا و بنسبة 63 %, وهي تستمر بمعدل وسطي 16,7 شهرا كما أنها ترتبط بمستوى العناية بالصحة الفموية (درجة تراكم اللويحة أو القلح). حيث بلغ متوسط مشعر اللويحة pi=1,98+64وأن الأسنان الأكثر تعرضا للإصابة هي الأرحاء ثم الضواحك والأنياب فالقواطع. تشير هذه الدراسة إلى نسبة مرتفعة لتواتر ظاهرة فرط الحساسية العاجية بين مرضى النسج حول السنية. هذا يعود إلى زيادة نسبة الانحسار اللثوي وانكشاف الجذر وما يرافق ذلك من فقدان لنسج السن بسبب المرض حول السني ما يشير إلى أن الأمراض حول السنية تزيد من احتمال ظهور فرط الحساسية . Dentinal hypersensitivity (DH) is one of the most important issue facing the clinical dental practice, due to the continuous troubles experienced by patients. Despite that this problem was regarded as an enigma, it did not receive enough attention. The aim of this study is to examine the frequency, prevalence, severity and distribution of dentinal hypersensitivity in the patients of periodontal specialty clinics (PSC) through analyzing the subjective estimation and intraoral examination in relation to the possible causal factors. Material and Methods. In addition to the traditional periodontal examination, 197 patients (average age of 17-65 yrs) referred to the Department of Periodontology were tested and analyzed. The subjective data was evaluated for DH by means of a questionnaire and intraoral clinical examinations. Furthermore, gingival recession and plaque scores were recorded. Results: The results showed that the prevalence of DH was found in 171 patients (86.8%) and in 130 patients (66%) according to the subjective data and according to the clinical intraoral examination respectively. The clinical hypersensitivity was coincided with gingival recession in 82 patients (63%) which lasted for an average of 16.7 months. It correlates with the oral hygiene and the mean plaque scores of PSC patients was high (1.98±64). The distribution of DH in tooth types was (in decreasing order) molars, premolars, canines and incisors. Conclusion: This study indicates the high percentage frequency of Dentin Hypersensitivity among our periodontal patients. This indicates that periodontal disease may increase the occurrence of hypersensitivity.